Meningkatkan Kemampuan Menulis Karangan Deskripsi Dengan Metode Latihan Terbimbing Menggunakan Gambar di SMAN 4 Pekanbaru - Hasibuan, Sefrida (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2017)
Writing one of the language skills that require practice to be mastered well. Writing requires skills such as word choice, paragraph linkage, language style and so on. In learning of Indonesian class X there is writing prose which one of them is prose description. Monitoring of Indonesian language learning in SMA Negeri 4 Pekanbaru, learners have problems in writing materials, especially the prose description which is evidenced by the low average value. This research is focused to know process of applying guided training method assisted image media in improving writing skill description. Proposed formulation is how the implementation of guided training methods help image media in improving ability to write essay writing description of students. Purpose of study to describe implementation of guided training methods assisted image media in improving ability to write essay description of students. This research is a type of Classroom Action Research by using method of observation, test results, questionnaires and documentation with data sources ie students of class X SMA Negeri 4 Pekanbaru with the number of students 32 people. Average value of students in the pre-cycle stage of 72, 91. After an action on cycle I, average student score rose 5.65 to 78.56. Next on cycle II, it increased by 49.8 to 85.28. The results obtained in cycle I using image media show an increase. Questionnaire assessment shows that the result of students' level of enthusiasm increases and students are able to focus more on learning process because of proper writing stages for students.